(untitled) (Asian Journal of Pharmaceutics (AJP), 2024)
Aim: This study focused on the formulation and evaluation of ocular in situ gels containing blueberry extract for potential therapeutic applications. Materials and Methods: Various parameters were assessed to determine the physical characteristics, stability, and performance of the formulated gels. These parameters included clarity, transparency, pH, viscosity, gelling capacity, in vitro and ex vivo drug release, sterility, ocular irritation, intraocular pressure (IOP) reduction, and pharmacokinetic profiles. Total number of six formulations were prepared and evaluated for different parameters. Percentage drug release of all the formulations were carried out by modified Franz diffusion cell using simulated tear fluid. Results and Discussion: B6 formulation has shown maximum percentage release of 98.35% in 8 h. Ex vivo studies indicated that 80.23% of the drug permeated from the formulations, demonstrating a sustained effect. Furthermore, in situ gel of blueberry extract (B6) demonstrated a good percentage reduction in IOP, with a value of 29.96 ± 2.88 % mmHg. The in situ gel formulation achieved a Cmax of 10.5 ± 1.28 mg/mL after 4 h, which was approximately 10 times higher than the Cmax of the timolol eye drop (0.908 mg/mL) obtained after 2 h. Conclusion: The results indicated that the in situ gels demonstrated favorable physical properties, stable pH, excellent gelling capacity, sustained drug release, and sterility. Furthermore, the gels exhibited no ocular irritation and effectively reduced IOP, offering potential benefits for glaucoma treatment. Pharmacokinetic analysis revealed enhanced drug bioavailability with the in situ gel formulations compared to conventional eye drops. Stability studies confirmed the formulation’s robustness under various environmental conditions. These findings highlight the suitability of the in situ gel formulations for ocular drug delivery, emphasizing their potential as effective and safe therapeutic options.